Considerações sobre a trajetória de desenvolvimento e processo de internacionalização da spin-off acadêmica Biomimetic Solutions - Lorena Viana Souza (2019)
Academic spin-offs (SOA) are companies set up to commercially exploit intellectual property developed within universities by turning knowledge into wealth. Understanding the path of these companies from universities to the market focused on internationalization is of great relevance to the generation of global startups. Biomimetic Solutions is a biotechnology SOA, which was born at CEFET-MG and started its international phase in the UK. Biomimetics technology is based on the growth of living tissue and has had its products varying along its trajectory from organ growth, artificial skin, dermal dressings to clean meat. This paper describes the development path and internationalization of Biomimetic, listing the main challenges and learning of each stage. The work describes each phase of the company, from academic research, pre-acceleration, acceleration and internationalization, characterizing the technology stage, the work done in each phase, the positive and negative points and the decision gates. From the described phases, an emphasis is given to the internationalization process, which culminated in the planning of Biomimetic from a global perspective.